Assessing Perceptions and Medication Disposal Habits in Rural Michigan - Cassandra L. Falk; Scott M. Sexton (University of Minnesota Libraries Publishing, 2023)
Background: Inadequate or inappropriate medication disposal is a public health concern that may lead to increased community risk of accidental poisonings, substance misuse, and environmental pollution.           Objective: The study's primary objective was to assess medication disposal knowledge and practices of Michigan residents living in rural, underserved areas. Secondary objectives included determining baseline perceptions of at-home drug disposal kits and examining the impact of an educational video intervention on at-home drug disposal kit perceptions. Methods: To measure the objectives, an online 15-question survey was deployed to the general public via convenience sampling from local organizations working with drug disposal. The survey questions assessed medication disposal knowledge and practices in underserved, rural Michigan. Participant responses were assessed categorically and numerically. Results: Inclusion criteria were met by 97 survey participants. Results indicated that Michigan rural residents, regardless of various demographic factors, would benefit from increased drug disposal education. Specifically, at-home drug disposal kits and medication drop boxes have the highest need for additional education. Perceptions related to home disposal safety and ease of use improved significantly with an educational video intervention. Conclusion: All rural residents, regardless of demographics, would benefit from increased drug disposal education. A short, educational video can impact thoughts and attitudes related to at-home drug disposal kits. Similar interventions may be successful in other rural, underserved areas.